Sosialisasi Penanganan Pasca Panen Bahan Baku Rempah Obat Tradisional - Fahrauk Faramayuda; Soraya Riyanti; Akhirul Kahfi Syam; Ari Sri Windyaswari; Yeni Karlina; Remare Halomoan Limbong; Anggita Esa Putri Fitrichia; Ananda Tunjung Pertiwi; Trialisa Aprilia; Ema Mutya; Renti Mutiara Dewi; Dwi Ayu Pratiwi; Usi Septiani; Esanda Zulfi Amedea; Yesi Wulandari; Adinda Fitriani; Ami Soega Dwigantina (Yayasan Kawanad, 2022)
Community service activities carried out by students of Universitas Jenderal Achmad Yani were carried out on August 29, 2022, taking place in a medicinal plant garden, Faculty of Pharmacy, Universitas Jenderal Achmad Yani which was attended by UMKM Spice Nusantara Bandung participants. The socialization carried out was the presentation and delivery of post-harvest processing materials (wet sorting, washing, drying, and dry sorting) and the standardization of traditional raw materials. Conventional medicine is a form of treatment efforts in the community to support health which is currently being recommended by the government. Communities can use the toga as an economical and efficient measure to maintain body immunity because the community can obtain and use the toga quickly and simply to maintain family health. The postharvest process greatly determines the existence of active compounds that are efficacious for treatment. Incorrect postharvest management can change, reduce, or destroy the active substance of a plant into a substance that has no therapeutic effect and can even endanger health. The results of the participant's level of understanding were carried out post-test with the results of what is the purpose of post-harvest processing (100%), the sequence of post-harvest processing (80%), what is the general drying temperature (100%), a medicinal plant has good quality and efficacy then we need to know (80%), and what is the function of the washing process (90%) with the conclusion that socialization activities can significantly increase the knowledge of participants from MSMEs regarding planting, post-harvest processing, and the properties of medicinal plants significantly.